Computational simulations for the development of novel solid-state smart NiTi-Al thermal diodes. (September 2017) - Frantziskonis, George N; Gur, Sourav
In this study, NiTi shape memory alloys coupled in series with Al are considered as building blocks for thermal diodes. It is shown that the strong nonlinearity in the temperature-dependent thermal properties of NiTi in conjunction with the very different thermal properties of Al can result into a thermal diode of high thermal rectification ratio. As a first level of study, Ni50 Ti50 is considered and the effects of various NiTi-Al geometrical configurations, initial temperature, and temperature difference at two ends on the thermal rectification ratio are studied numerically. Within the adopted temperature range (300–400 K, where phase transformation in NiTi occurs), it is shown that NiTi-Al thermal diodes are feasible with rectification ratio up to 4.8, which is quite higher than the ratios in currently known solid-state thermal diodes. This fundamental computational study could provide an important basis and motivation for the development of the next generation of high-temperature solid-state thermal diodes based on smart material such as NiTi shape memory alloys or others.